2020
DOI: 10.1051/e3sconf/202019603004
|View full text |Cite
|
Sign up to set email alerts
|

Principles of organizing earthquake forecasting based on multiparameter sensor-WEB monitoring data

Abstract: The paper describes an approach that allows, basing on the data of multiparameter monitoring of atmospheric and ionospheric parameters and using ground-based and satellite measurements, to select from the data stream a time interval indicating the beginning of the final stage of earthquake preparation, and finally using intelligent data processing to carry out a short-term forecast for a time interval of 2 weeks to 1 day before the main shock. Based on the physical model of the lithosphere-atmospheric-ionosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…One can see that they fall into the range of 20%-22% of positive deviation. This coincides with our previous earthquake results in the Kamchatka region [43]. We can conclude that by estimating the ionospheric anomaly size on the level of deviation 20%-22%, we can estimate the earthquake magnitude.…”
Section: Determination Of Earthquake Forecast Parameterssupporting
confidence: 91%
“…One can see that they fall into the range of 20%-22% of positive deviation. This coincides with our previous earthquake results in the Kamchatka region [43]. We can conclude that by estimating the ionospheric anomaly size on the level of deviation 20%-22%, we can estimate the earthquake magnitude.…”
Section: Determination Of Earthquake Forecast Parameterssupporting
confidence: 91%
“…However, newly formed ions have different chemical potentials; what is to introduce should consider in the one-component approximation we introduce the correction to the chemical potential. The increase of the water molecules chemical potential indicates the strength of the nucleation process and can be used as an indicator of an imminent earthquake according to Boyarchuk et al, 2010 and demonstrated already within multiparameter analysis (Ouzounov et al, 2018a;Pulinets et al, 2020).…”
Section: Air Temperature Observationsmentioning
confidence: 98%